Estrategias de control para ampliar la base tributaria en médicos perceptores de renta de cuarta categoría, periodo 2015-2016 - Tasa Catanzaro, Magaly (2016)
The problem addressed in the investigation is posed in the question: how can the non-compilance of the tax declaration of the Generators of the Fourth Category be reduced? To avoid evasion, improve control and increase collection?